Studi Awal: Identifikasi Keragaman Bakteri Saliva Wanita Usia Lanjut Menggunakan Teknologi 16S rRNA Sequencing Oxford Nanopore - Chris Adhiyanto., Ph.D; Laifa A. Hendarmin; Zeti Harriyati; Erike A. Suwarsono; Auliyani Andam Suri; Yudhi Nugraha; Dwirini Retno Gunarti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The elderly are a population particularly susceptible to diseases resulting from the decline in immune system function. The mouth is one of the areas of the body that is the entry point for microorganisms into the body. It is known that the oral microbiome greatly affects oral and systemic health. The oral bacterial profile is important to understand its role in maintaining health and causing disease. Therefore, maintaining oral health is very important, especially in our study of the elderly. Utilizing advanced sequencing techniques such as Oxford Nanopore Technology (ONT) offers the opportunity to reveal bacterial diversity comprehensively. This study aims to identify the oral microbiome in a group of elderly women. Knowledge of the oral microbiota profile could help spread awareness of the benefits of maintaining good dental hygiene, especially in older adults. Methods: Seven elderly housewives had their unstimulated saliva samples taken in the morning and kept at -80°C. The phenol-chloroform technique was used to isolate the DNA, and a Qubit Fluorometer was used to measure purity and concentration. By employing ONT for 16S rRNA sequencing and Epi2Me software for analysis, taxonomic mapping of the bacterial diversity was accomplished.  Results: According to the taxonomic analysis, Streptococcus and Veillonella were the most common genera in the samples. It was common to find species like Veillonella parvula, Veillonella atypica, Streptococcus mitis, and Streptococcus rubneri. These genera contributed to the dynamics of oral biofilms by exhibiting complex ecological interactions. With advanced sequencing technologies, this work highlights the diversity of oral bacteria in elderly women in Indonesia while providing a new perspective. Notwithstanding a few limitations, these findings provide insight into the ecological dynamics of the oral microbiota, potentially leading to clinical applications in the treatment and prevention of disease.